A V-Ag-O / TiO2 catalyst and its application

By loading V-Ag-O on mesoporous TiO2 and performing alkali modification, the problems of small surface area and low reaction activity caused by the TiO2 particle morphology in existing catalysts were solved, and a highly efficient toluene vapor-phase oxidation to benzaldehyde reaction was achieved.

CN114160132BInactive Publication Date: 2025-04-18SINOPEC YANGZI PETROCHEMICAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010951408.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-11
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among the existing V-Ag-O catalysts with TiO2 as support, TiO2 mainly exists in the form of amorphous particles, resulting in a small specific surface area and limiting the reactivity of the catalyst.

Method used

By loading V-Ag-O on mesoporous TiO2 and performing alkali modification in alkali solution, the surface dispersion of active species is increased, the low-temperature reduction is improved, and the catalyst surface vacancy defects are increased, so as to enhance the migration of surface oxygen.

Benefits of technology

The reaction activity and selectivity of the catalyst are improved, and efficient catalysis of toluene gas-phase oxidation to make benzaldehyde is achieved. The toluene conversion rate is greater than 15%, the benzaldehyde selectivity is greater than 60%, and the benzaldehyde yield is greater than 10%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002677079020000031
    Figure BDA0002677079020000031
Patent Text Reader

Abstract

The invention belongs to the field of catalysts for preparing benzaldehyde by gas phase oxidation of toluene, and specifically relates to a V-Ag-O / TiO 2 Catalyst and its application. The V-Ag-O / TiO 2 The catalyst is prepared by the following steps: (1) dissolving a vanadium-containing precursor and a silver precursor in aqueous ammonia to obtain a mixed solution; (2) adding mesoporous TiO 2 , stirring at a constant temperature, drying, and calcining; (3), stirring the product obtained in step (2) in an alkaline solution, wherein the mass volume ratio of the catalyst to the alkaline solution is 1:5 to 1:15 g / mL, and then centrifuging, washing with deionized water, and drying to obtain the V-Ag-O / TiO 2 Catalyst. The catalyst of the present invention has good reaction performance in the reaction of preparing benzaldehyde by gas-phase oxidation of toluene, with a toluene conversion rate of more than 15%, a benzaldehyde selectivity of more than 60%, and a benzaldehyde yield of more than 10%, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts for preparing benzaldehyde by gas-phase oxidation of toluene, and specifically relates to an alkali-modified V-Ag-O / TiO2 catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, the benzaldehyde production processes that have been studied more include benzyl alcohol oxidation, styrene oxidation, benzoic acid or ester reduction, electrolytic synthesis and toluene gas phase oxidation. The first three processes are limited by the high cost of raw materials and the market competitiveness of the equipment; the electric synthesis method has high energy consumption and is not conducive to large-scale production; the toluene gas phase oxidation method is a production process with high atomic economy, and the obtained benzaldehyde product does not contain chlorine.

[0003] Vanadium-based catalysts are a type of catalyst for the gas-phase oxidation of toluene to benzaldehyde that has been studied more. The vanadium-based catalyst loaded on TiO2 after adding silver additives can further improve the catalyst's reducibility, so that the catalyst can obtain a higher conversion rate and higher selectivity at a lower temperature. Studies have found that the V-Ag-O / 20% TiO2 catalyst has a benzaldehyde selectivity of up to 95% at 440°C when the toluene conversion rate is 7.3% (Xue, M., Yu, J., Chen, H. et al. Surface Acidic and Redox Properties of V–Ag–O / TiO2 Catalysts for the Selective Oxidation of Toluene to Benzaldehyde. Catal Lett, 2009, Vol. 128, pp. 373-378). However, in the reported toluene gas-phase oxidation catalysts loaded with V on TiO2 as a carrier, TiO2 mainly exists in the form of amorphous particles with a small specific surface area. The low specific surface area reduces the number of active V species dispersed in a monolayer, thereby limiting the reaction activity of the catalyst. Summary of the invention

[0004] The present invention proposes a catalyst which is prepared by loading V-Ag-O with mesoporous TiO2 and performing alkali modification on the catalyst. The catalyst improves the reaction performance of the catalyst in catalyzing gas-phase oxidation of toluene to prepare benzaldehyde by increasing the surface dispersion of V-Ag-O active species, improving the low-temperature reducibility of the catalyst, increasing the vacancy defects on the catalyst surface, enhancing the migration of surface oxygen, and reducing the surface acidity of the catalyst.

[0005] The specific technical solutions of the present invention are as follows:

[0006] A V-Ag-O / TiO2 catalyst is prepared by the following steps:

[0007] (1) dissolving a vanadium- and silver-containing precursor in aqueous ammonia to obtain a mixed solution;

[0008] (2) Add mesoporous TiO2 to the solution obtained in step (1), stir at a constant temperature, dry, and calcine;

[0009] (3) Stirring the product obtained in step (2) in an alkaline solution with a mass volume ratio of the catalyst to the alkaline solution of 1:5 to 1:15 g / mL, then centrifuging, washing with deionized water and drying to obtain the V-Ag-O / TiO2 catalyst.

[0010] Wherein, in the mixed solution of step (1), the molar concentration of vanadium is 1.099-4.659 mol / L, the molar concentration of silver is 0.0863-0.3659 mol / L, and the mass fraction of ammonia water is 20-40%.

[0011] Wherein, in step (2), 214.6 to 910.0 g of mesoporous TiO2 is added to the solution obtained in (1) per mol of vanadium.

[0012] Wherein, in step (2), the specific surface area of ​​the mesoporous TiO2 is 60 to 90 m 2 / g, pore volume is 0.28~0.45cm 3 / g.

[0013] The vanadium precursor includes at least one of vanadium pentoxide and ammonium metavanadate; and the silver precursor includes at least one of silver oxide and silver nitrate.

[0014] The constant temperature stirring and drying in step (2) is performed at a temperature of 80 to 120° C.; and the calcination in step (2) is performed at a temperature of 350 to 450° C. for 3 to 6 hours in an air atmosphere.

[0015] Wherein, the alkaline solution described in step (3) is sodium hydroxide or potassium hydroxide solution, and the concentration of the alkaline solution is 2.5 to 15 mol / L.

[0016] The stirring time in step (3) is 0.5 to 1.5 hours; the drying temperature in step (3) is 90 to 120° C., and the drying time is 2 to 5 hours.

[0017] An application of any of the aforementioned V-Ag-O / TiO2 catalysts for preparing benzaldehyde.

[0018] The catalyst is loaded into the reactor and calcined at 380-450°C under normal pressure for 1-2 hours with air flow rate of 25-50 L / (g cat*h) Then switch to reaction gas, the volume fraction of toluene in the reaction gas is 0.06-0.15%, the rest is air, and the toluene feed amount is 0.12-0.25 g / (g cat *h), reaction space velocity 34~68L / (g cat *h).

[0019] Beneficial Effects

[0020] Compared with the prior art, which can only add about 1% of potassium nitrate, sodium nitrate and other alkaline additives for impregnation of vanadium, molybdenum and manganese subgroups, or can only carry out acid etching, the present invention has a breakthrough in that the V-Ag-O / TiO2 catalyst surface is alkaline-etched by placing the V-Ag-O / TiO2 in an alkaline environment formed by an alkaline solution, which can not only reduce its surface acidity, but also form more vacancy defects on its surface, thereby facilitating the migration of oxygen species on the catalyst surface, enhancing the catalyst reduction ability, and improving the catalyst reaction activity.

[0021] In addition, the alkali-modified V-Ag-O / TiO2 catalyst provided by the present invention has good reaction performance for the gas-phase oxidation of toluene to produce benzaldehyde, with a toluene conversion rate greater than 15%, a benzaldehyde selectivity greater than 60%, and a benzaldehyde yield greater than 10%. DETAILED DESCRIPTION

[0022] In the following examples, the vanadium pentoxide, ammonium metavanadate, ammonia water, sodium hydroxide, and potassium hydroxide used were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were all analytically pure; mesoporous TiO2 was purchased from Degussa, Germany, and was analytically pure; silver oxide and silver nitrate were purchased from Shanghai Aladdin Chemical Reagent Co., Ltd., and were all analytically pure. The reactor used was a micro-reactor evaluation device sold by Beijing Tuochuan Scientific Research Equipment Co., Ltd., and the chromatograph used was a 7890A sold by Agilent Technologies.

[0023] In the following examples, the calculation method based on the chromatographic analysis results includes the following:

[0024] 1. The content of toluene at the reaction inlet is determined by the external standard method. The composition and chromatographic peak area of ​​toluene standard gas are shown in Table 1. The meanings of the symbols are as follows: A chromatographic peak area, M molecular weight, y mole fraction, V feed volume flow rate, F mass flow rate. Toluene flow rate F at the reaction inlet 甲苯 =V*y 甲苯标样 *(A 甲苯进口 / A 甲苯标样 ) / 22.4*M 甲苯 . The conversion rate of toluene reaction is X = 1-A 甲苯出口 / A 甲苯进口 .

[0025] Table 1 Toluene standard gas composition and chromatographic peak area

[0026]

[0027] 2. CO x The analysis was performed using the external standard method, with a standard gas flow rate of 80 mL / min. The standard gas composition and the correction factors of each component are shown in Table 2. The gas at the outlet of the gas-liquid separator was collected with a gas sampling bag and fed into the chromatographic analysis at a flow rate of 80 mL / min. The CO in the reaction tail gas could be calculated based on the CO and CO2 peak areas. x Concentration COx =A CO / A CO标样 *y CO +A CO2 / A CO2标样 *y CO2 . S stands for selectivity. COX =V*y COx / 22.4*M 甲苯 / (F 甲苯 *X).

[0028] Table 2 CO x Standard gas composition and peak area of ​​each component

[0029] <![CDATA[N2]]> CO <![CDATA[CO2]]> Mole fraction% 96.96 1.01 2.03 Retention time (min) 1.116 1.948 4.074 Peak area 50123.2 561.5268 1058.331

[0030] 3. The composition of the prepared organic product standard sample and the correction factors of each component are shown in Table 3. i represents benzene, benzaldehyde, benzoic acid or other components, x represents the area percentage of each product component after deducting toluene from the chromatogram, and f is the correction factor. ω represents the area percentage of each product component after deducting toluene from the chromatogram, and f is the correction factor. x The mass fraction of each component of the external product. n represents the number of carbon atoms in the molecular formula of the component. i =x i *f i / ∑(x i *f i ), S i =ω i / M i *n i / 7 / (∑(ω i / M i *n i / 7)*(1-S COX )).

[0031] Table 3 Composition of organic product standard samples and correction factors of each component

[0032] Toluene Benzaldehyde benzoic acid Mass(g) 0.7224 0.1247 0.0598 Retention time (min) 2.631 6.123 9.058 Peak area A 28726 3108 1286 Correction factor f 2.51474E-05 4.01E-05 4.65E-05

[0033] Embodiment 1:

[0034] Dissolve 1g of vanadium pentoxide and 0.1g of silver oxide in 10mL of ammonia water, where the mass fraction of ammonia is 20%. At this time, the molar concentration of vanadium in the solution is 1.099mol / L, and the molar concentration of silver is 0.0863mol / L. Add 10g of mesoporous TiO2 to the solution. The specific surface area of ​​the mesoporous TiO2 is 60m 2 / g, pore volume 0.28cm 3 / g, 80°C constant temperature stirring and drying, and then calcining at 350°C for 6h in air atmosphere. The obtained product is stirred in sodium hydroxide solution for 0.5h, the mass volume ratio of the catalyst to the sodium hydroxide solution is 1:5, the concentration of the sodium hydroxide solution is 2.5mol / L, and then centrifuged, washed with deionized water and dried at 90°C for 5h to obtain the V-Ag-O / TiO2 catalyst of the present invention. The element content of the obtained V-Ag-O / TiO2 catalyst is determined by ICP method, wherein the active component V is calculated as 10% of the weight of the carrier TiO2 in terms of V2O5, and the auxiliary agent Ag is calculated as 1% of the weight of TiO2 in terms of Ag2O.

[0035] Preparation of benzaldehyde using the prepared V-Ag-O / TiO2 catalyst:

[0036] 2 g of the prepared catalyst was loaded into a reactor and calcined at 380°C for 1 h under normal pressure with an air flow rate of 25 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was -5°C, and the bubbling air flow rate was 10L / (g cat *h), toluene feed amount 0.12g / (g cat *h), supplementary air flow rate 38.7L / (g cat *h), the volume fraction of toluene in the feed is 0.06%, and the reaction space velocity is 48.7L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 5°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 50°C, and the product is kept warm at 250°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0037] In the present embodiment, the chromatographic analysis results are as follows: the reaction inlet toluene chromatographic peak area is 3555, the reaction outlet toluene chromatographic peak area is 3022, the CO peak area is 0, the CO2 peak area is 7.8, and the area percentage of each product component after deducting toluene is benzene 14.5%, benzaldehyde 75%, benzoic acid 2.3%, and other components 8.2%. According to the chromatographic analysis results, the toluene conversion rate is 15%, the benzaldehyde selectivity is 68.1%, and the benzaldehyde yield is 10.2%.

[0038] Embodiment 2:

[0039] 5.45g of ammonium metavanadate and 0.62g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 40%, the molar concentration of vanadium in the solution was 4.659mol / L, and the molar concentration of silver was 0.3659mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 90m 2 / g, pore volume 0.45cm 3 / g, stirred and dried at a constant temperature of 120°C, and then calcined at 450°C for 3h in an air atmosphere. The obtained product was stirred in a potassium hydroxide solution for 1.5h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:15, the concentration of the potassium hydroxide solution was 15mol / L, and then centrifuged, washed with deionized water and dried at 120°C for 2h to obtain the V-Ag-O / TiO2 catalyst of the present invention. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5 with respect to the weight of the carrier TiO2 of 42.4%, and the auxiliary agent Ag was calculated as Ag2O with respect to the weight of TiO2 of 4.24%.

[0040] Preparation of benzaldehyde using the prepared V-Ag-O / TiO2 catalyst:

[0041] 2 g of the prepared catalyst was loaded into a reactor and calcined at 450 °C for 2 h under normal pressure with an air flow rate of 50 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 50°C and the bubbling air flow rate was 15L / (g cat *h), toluene feed rate 0.25g / (g cat *h), supplementary air flow rate 25.5L / (g cat *h), the volume fraction of toluene in the feed is 0.15%, and the reaction space velocity is 40.5L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is -10°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed insulation temperature is 120°C, and the product insulation temperature is 350°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0042] In the present embodiment, the chromatographic analysis results are as follows: the reaction inlet toluene chromatographic peak area is 8891, the reaction outlet toluene chromatographic peak area is 6828, the CO peak area is 0, the CO2 peak area is 32.3, and the area percentage of each product component after deducting toluene is benzene 20.3, benzaldehyde 65.3%, benzoic acid 11.3%, and other components 3.1%. According to the chromatographic analysis results, the toluene conversion rate is calculated to be 23.2%, the benzaldehyde selectivity is 60%, and the benzaldehyde yield is 13.9%.

[0043] Embodiment 3:

[0044] 4.5g of ammonium metavanadate and 0.59g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 30%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100°C, and then calcined at 420°C for 4h in an air atmosphere. The obtained product was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 12mol / L, and then centrifuged, washed with deionized water and dried at 100°C for 4h to obtain the V-Ag-O / TiO2 catalyst of the present invention. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5 with a weight of 35% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O with a weight of 4% of the weight of TiO2.

[0045] Preparation of benzaldehyde using the prepared V-Ag-O / TiO2 catalyst:

[0046] 2 g of the prepared catalyst was loaded into a reactor and calcined at 430°C for 1.5 h under normal pressure with an air flow rate of 40 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 18L / (g cat *h), toluene feed rate 0.2g / (g cat *h), supplementary air flow rate 30.6L / (g cat *h), the volume fraction of toluene in the feed is 0.1%, and the reaction space velocity is 48.6L / (g cat*h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0047] In the present embodiment, the chromatographic analysis results are as follows: the reaction inlet toluene chromatographic peak area is 5933, the reaction outlet toluene chromatographic peak area is 4503, the CO peak area is 0, the CO2 peak area is 30.7, and the area percentage of each product component after deducting toluene is benzene 9.6%, benzaldehyde 86.7%, benzoic acid 1.2%, and other components 2.5%. According to the chromatographic analysis results, the toluene conversion rate is 24.1%, the benzaldehyde selectivity is 73.2%, and the benzaldehyde yield is 17.6%.

[0048] Embodiment 4:

[0049] 4.5g of ammonium metavanadate and 0.59g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 30%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100°C, and then calcined at 420°C for 4h in an air atmosphere. The obtained product was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 8mol / L, and then centrifuged, washed with deionized water and dried at 100°C for 4h to obtain the V-Ag-O / TiO2 catalyst of the present invention. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5 with a weight of 35% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O with a weight of 4% of the weight of TiO2.

[0050] The prepared catalyst was evaluated according to the reaction conditions described in Example 3. The chromatographic analysis results are as follows: the chromatographic peak area of ​​toluene at the reaction inlet is 5933, the chromatographic peak area of ​​toluene at the reaction outlet is 4326, the CO peak area is 0, the CO2 peak area is 37, and the area percentage content of each product component after deducting toluene is 8.7% benzene, 85.4% benzaldehyde, 3.1% benzoic acid, and 2.8% other components. According to the chromatographic analysis results, the toluene conversion rate is 27.1%, the benzaldehyde selectivity is 70.9%, and the benzaldehyde yield is 19.2%.

[0051] Embodiment 5:

[0052] 4.5g of ammonium metavanadate and 0.59g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 30%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100°C, and then calcined at 420°C for 4h in an air atmosphere. The obtained product was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 6mol / L, and then centrifuged, washed with deionized water and dried at 100°C for 4h to obtain the V-Ag-O / TiO2 catalyst of the present invention. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5 with a weight of 35% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O with a weight of 4% of the weight of TiO2.

[0053] The prepared catalyst was evaluated according to the reaction conditions described in Example 3. The chromatographic analysis results are as follows: the chromatographic peak area of ​​toluene at the reaction inlet is 5933, the chromatographic peak area of ​​toluene at the reaction outlet is 4326, the CO peak area is 0, the CO2 peak area is 37, and the area percentage content of each product component after deducting toluene is 7.9% benzene, 84.7% benzaldehyde, 2.6% benzoic acid, and 4.8% other components. According to the chromatographic analysis results, the toluene conversion rate is 20.9%, the benzaldehyde selectivity is 67.8%, and the benzaldehyde yield is 14.2%.

[0054] Embodiment 6:

[0055] 4.5g of ammonium metavanadate and 0.44g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 40%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100℃, and then calcined at 420℃ in an air atmosphere for 4h to obtain a V-Ag-O / TiO2 catalyst. The prepared V-Ag-O / TiO2 catalyst was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 8mol / L, and then centrifuged, washed with deionized water and dried at 100℃ for 4h to obtain an alkali-modified V-Ag-O / TiO2 catalyst. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5, which was 35% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O, which was 3% of the weight of TiO2.

[0056] The prepared catalyst was evaluated according to the reaction conditions described in Example 3. The chromatographic analysis results are as follows: the chromatographic peak area of ​​toluene at the reaction inlet is 5933, the chromatographic peak area of ​​toluene at the reaction outlet is 4326, the CO peak area is 0, the CO2 peak area is 37, and the area percentage content of each product component after deducting toluene is 7.9% benzene, 84.7% benzaldehyde, 2.6% benzoic acid, and 4.8% other components. According to the chromatographic analysis results, the toluene conversion rate is 29.1%, the benzaldehyde selectivity is 71.2%, and the benzaldehyde yield is 20.7%.

[0057] Embodiment 7:

[0058] 4.5g of ammonium metavanadate and 0.29g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 40%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 10g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100℃, and then calcined at 420℃ in an air atmosphere for 4h to obtain a V-Ag-O / TiO2 catalyst. The prepared V-Ag-O / TiO2 catalyst was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 8mol / L, and then centrifuged, washed with deionized water and dried at 100℃ for 4h to obtain an alkali-modified V-Ag-O / TiO2 catalyst. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5, which was 35% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O, which was 2% of the weight of TiO2.

[0059] The prepared catalyst was evaluated according to the reaction conditions described in Example 3.

[0060] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5933, the peak area of ​​toluene at the reaction outlet is 4355, the peak area of ​​CO is 0, the peak area of ​​CO2 is 39.6, and the area percentage of each product component after deducting toluene is 7.3% benzene, 83.5% benzaldehyde, 2.3% benzoic acid, and 6.9% other components. According to the results of chromatographic analysis, the toluene conversion rate is 26.6%, the benzaldehyde selectivity is 67.3%, and the benzaldehyde yield is 17.9%.

[0061] Embodiment 8:

[0062] 4.5g of ammonium metavanadate and 0.44g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 40%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 11g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100℃, and then calcined at 420℃ in an air atmosphere for 4h to obtain a V-Ag-O / TiO2 catalyst. The prepared V-Ag-O / TiO2 catalyst was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 8mol / L, and then centrifuged, washed with deionized water and dried at 100℃ for 4h to obtain an alkali-modified V-Ag-O / TiO2 catalyst. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was 31.8% of the weight of the carrier TiO2 in terms of V2O5, and the auxiliary agent Ag was 2.7% of the weight of TiO2 in terms of Ag2O.

[0063] The prepared catalyst was evaluated according to the reaction conditions described in Example 3.

[0064] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5933, the peak area of ​​toluene at the reaction outlet is 4402, the peak area of ​​CO is 0, the peak area of ​​CO2 is 35.5, and the area percentage of each product component after deducting toluene is 6.9% benzene, 83.2% benzaldehyde, 2.1% benzoic acid, and 7.8% other components. According to the results of chromatographic analysis, the toluene conversion rate is 25.8%, the benzaldehyde selectivity is 68.2%, and the benzaldehyde yield is 17.6%.

[0065] Embodiment 9:

[0066] 4.5g of ammonium metavanadate and 0.44g of silver nitrate were dissolved in 10mL of ammonia water, the mass fraction of ammonia in the ammonia water was 40%, the molar concentration of vanadium in the solution was 3.846mol / L, and the molar concentration of silver was 0.3452mol / L. 9g of mesoporous TiO2 carrier was added to the solution, and the specific surface area of ​​mesoporous TiO2 was 81m 2 / g, pore volume 0.39cm 3 / g, stirred and dried at a constant temperature of 100℃, and then calcined at 420℃ in an air atmosphere for 4h to obtain a V-Ag-O / TiO2 catalyst. The prepared V-Ag-O / TiO2 catalyst was stirred in a potassium hydroxide solution for 1h, the mass volume ratio of the catalyst to the potassium hydroxide solution was 1:12, the concentration of the potassium hydroxide solution was 8mol / L, and then centrifuged, washed with deionized water and dried at 100℃ for 4h to obtain an alkali-modified V-Ag-O / TiO2 catalyst. The element content of the obtained V-Ag-O / TiO2 catalyst was determined by the ICP method, wherein the active component V was calculated as V2O5, which was 38.9% of the weight of the carrier TiO2, and the auxiliary agent Ag was calculated as Ag2O, which was 3.3% of the weight of TiO2.

[0067] The prepared catalyst was evaluated according to the reaction conditions described in Example 3.

[0068] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5933, the peak area of ​​toluene at the reaction outlet is 4142, the peak area of ​​CO is 0, the peak area of ​​CO2 is 48, and the area percentage of each product component after deducting toluene is 9.2% benzene, 79.3% benzaldehyde, 4.6% benzoic acid, and 6.9% other components. According to the results of chromatographic analysis, the toluene conversion rate is 30.2%, the benzaldehyde selectivity is 63.1%, and the benzaldehyde yield is 19.1%.

[0069] Embodiment 10:

[0070] 2 g of the catalyst prepared in Example 6 was loaded into a reactor and calcined at 430°C for 1.5 h under normal pressure with an air flow rate of 40 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 22L / (g cat *h), toluene feed amount 0.22g / (g cat *h), supplementary air flow rate 26.6L / (g cat *h), the volume fraction of toluene in the feed is 0.11%, and the reaction space velocity is 48.6L / (g cat*h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0071] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 6525, the peak area of ​​toluene at the reaction outlet is 4809, the peak area of ​​CO is 0, the peak area of ​​CO2 is 21.4, and the area percentage of each product component after deducting toluene is 8.7% benzene, 79% benzaldehyde, 5.1% benzoic acid, and 7.2% other components. According to the results of chromatographic analysis, the toluene conversion rate is 26.3%, the benzaldehyde selectivity is 72.1%, and the benzaldehyde yield is 19.0%.

[0072] Embodiment 11:

[0073] 2 g of the catalyst prepared in Example 6 was loaded into a reactor and calcined at 430°C for 1.5 h under normal pressure with an air flow rate of 40 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 14L / (g cat *h), toluene feed amount 0.17g / (g cat *h), supplementary air flow rate 34.6L / (g cat *h), the volume fraction of toluene in the feed is 0.085%, and the reaction space velocity is 48.6L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0074] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5045, the peak area of ​​toluene at the reaction outlet is 3466, the peak area of ​​CO is 0, the peak area of ​​CO2 is 39.6, and the area percentage of each product component after deducting toluene is 9.3% benzene, 78.7% benzaldehyde, 4.6% benzoic acid, and 7.4% other components. According to the results of chromatographic analysis, the toluene conversion rate is 31.3%, the benzaldehyde selectivity is 63.7%, and the benzaldehyde yield is 19.9%.

[0075] Embodiment 12:

[0076] 2 g of the catalyst prepared in Example 6 was loaded into a reactor and calcined at 430°C for 1.5 h under normal pressure with an air flow rate of 40 L / (gcat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 18L / (g cat *h), toluene feed rate 0.2g / (g cat *h), supplementary air flow rate 50L / (g cat *h), the volume fraction of toluene in the feed is 0.07%, and the reaction space velocity is 68.0L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0077] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 4243, the peak area of ​​toluene at the reaction outlet is 3386, the peak area of ​​CO is 0, the peak area of ​​CO2 is 16.7, and the area percentage of each product component after deducting toluene is 6.1% benzene, 89.3% benzaldehyde, 2.7% benzoic acid, and 1.9% other components. According to the results of chromatographic analysis, the toluene conversion rate is 20.2%, the benzaldehyde selectivity is 76.3%, and the benzaldehyde yield is 15.4%.

[0078] Embodiment 13:

[0079] 2 g of the catalyst prepared in Example 6 was loaded into a reactor and calcined at 430°C for 1.5 h under normal pressure with an air flow rate of 40 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 18L / (g cat *h), toluene feed rate 0.2g / (g cat *h), supplementary air flow rate 16L / (g cat *h), the volume fraction of toluene in the feed is 0.14%, and the reaction space velocity is 34.0L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0080] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 8475, the peak area of ​​toluene at the reaction outlet is 5813, the peak area of ​​CO is 0, the peak area of ​​CO2 is 46.4, and the area percentage of each product component after deducting toluene is 10.7% benzene, 70.1% benzaldehyde, 9.3% benzoic acid, and 9.9% other components. According to the chromatographic analysis results, the toluene conversion rate is 31.4%, the benzaldehyde selectivity is 61.2%, and the benzaldehyde yield is 19.2%.

[0081] Embodiment 14:

[0082] 2 g of the catalyst prepared in Example 6 was loaded into a reactor and calcined at 440°C for 1.5 h under normal pressure with an air flow rate of 40 L / (g cat *h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene. The saturation temperature of toluene was 30°C, and the bubbling air flow rate was 18L / (g cat *h), toluene feed rate 0.2g / (g cat *h), supplementary air flow rate 30.6L / (g cat *h), the volume fraction of toluene in the feed is 0.1%, and the reaction space velocity is 48.6L / (g cat *h); after the reaction product is condensed by the condenser, it enters the gas-liquid separator to separate the liquid product and tail gas, and the reactor condensation temperature is 0°C. The reaction feed and product are kept warm and sent to the chromatograph online to analyze the content of each organic component therein, the feed is kept warm at 100°C, and the product is kept warm at 300°C; the reaction tail gas is sent to the chromatograph online to analyze the CO and CO2 content therein.

[0083] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5933, the peak area of ​​toluene at the reaction outlet is 4100, the peak area of ​​CO is 0, the peak area of ​​CO2 is 41.2, and the area percentage of each product component after deducting toluene is benzene 11.6%, benzaldehyde 72.3%, benzoic acid 12.1%, and other components 4%. According to the results of chromatographic analysis, the toluene conversion rate is 30.9%, the benzaldehyde selectivity is 60.7%, and the benzaldehyde yield is 18.8%.

[0084] Embodiment 15:

[0085] 2g of the catalyst prepared in Example 6 was loaded into a reactor, and the reactor was first calcined at 420°C with air for 1.5h at a normal pressure and an air flow rate of 40L / (gcat*h); then, toluene and supplementary air were mixed and sent into the reactor by bubbling air in toluene, with a toluene saturation temperature of 30°C, a bubbling air flow rate of 18L / (gcat*h), a toluene feed amount of 0.2g / (gcat*h), a supplementary air flow rate of 30.6L / (gcat*h), a volume fraction of toluene in the feed of 0.1%, and a reaction space velocity of 48.6L / (gcat*h); the reaction product was condensed in a condenser and then entered a gas-liquid separator for separation to obtain a liquid product and tail gas, and the reactor condensation temperature was 0°C. The reaction feed and product were kept warm and entered into a chromatographic online analysis of the content of each organic component therein, with a feed insulation temperature of 100°C and a product insulation temperature of 300°C; the reaction tail gas was entered into a chromatographic online analysis of the CO and CO2 content therein.

[0086] The results of chromatographic analysis are as follows: the peak area of ​​toluene at the reaction inlet is 5933, the peak area of ​​toluene at the reaction outlet is 4337, the peak area of ​​CO is 0, the peak area of ​​CO2 is 38.1, and the area percentage of each product component after deducting toluene is 7.3% benzene, 87.6% benzaldehyde, 3.7% benzoic acid, and 1.4% other components. According to the results of chromatographic analysis, the toluene conversion rate is 26.9%, the benzaldehyde selectivity is 72.6%, and the benzaldehyde yield is 19.5%.

Claims

1. A V-Ag-O / TiO2 catalyst, characterized in that: Prepare by the following steps: (1) dissolving a vanadium-containing precursor and a silver precursor in aqueous ammonia to obtain a mixed solution; (2) Add mesoporous TiO2 to the solution obtained in step (1), stir at a constant temperature, dry, and calcine; (3) stirring the product obtained in step (2) in an alkaline solution with a mass volume ratio of the catalyst to the alkaline solution of 1:5 to 1:15 g / mL, then centrifuging, washing with deionized water and drying to obtain the V-Ag-O / TiO2 catalyst; In the mixed solution of step (1), the molar concentration of vanadium ions is 1.099-4.659 mol / L, the molar concentration of silver ions is 0.0863-0.3659 mol / L, and the mass fraction of ammonia water is 20-40%; In step (2), 214.6-910.0 g of mesoporous TiO2 is added to the solution obtained in step (1) per mol of vanadium; The alkaline solution in step (3) is a sodium hydroxide or potassium hydroxide solution, and the concentration of the alkaline solution is 2.5-15 mol / L.

2. The catalyst according to claim 1, characterized in that In step (2), the specific surface area of ​​the mesoporous TiO2 is 60-90 m 2 / g, pore volume is 0.28~0.45cm 3 / g.

3. The catalyst according to claim 1, characterized in that The vanadium precursor includes at least one of vanadium pentoxide or ammonium metavanadate; and the silver precursor includes at least one of silver oxide or silver nitrate.

4. The catalyst according to claim 1, characterized in that The temperature of the constant temperature stirring and drying in step (2) is 80-120°C; the calcination in step (2) is performed in an air atmosphere at 350-450°C for 3-6 hours.

5. The catalyst according to claim 1, characterized in that The stirring time in step (3) is 0.5-1.5 h; the drying temperature in step (3) is 90-120° C., and the drying time is 2-5 h.

6. Use of the V-Ag-O / TiO2 catalyst according to any one of claims 1 to 5, characterized in that: Used in the preparation of benzaldehyde.

7. The use of the V-Ag-O / TiO2 catalyst according to claim 6, characterized in that: The catalyst is loaded into the reactor and calcined at 380-450°C under normal pressure for 1-2 hours with air flow rate of 25-50 L / (g cat *h) Then switch to reaction gas, the volume fraction of toluene in the reaction gas is 0.06~0.15%, the rest is air, and the toluene feed amount is 0.12~0.25g / (g cat *h), reaction space velocity 34~68L / (g cat* h).

Citation Information

Patent Citations

  • Vanadium-silver doped titanium nanotube catalyst, preparation method and application thereof

    CN109201055A

  • Mesoporous bentonite and preparation method thereof

    CN109422270A